The trypanosome Pumilio domain protein PUF5. - Bhaskar Anand Jha; Stuart K Archer; Christine E Clayton (PLoS ONE, 2013)
PUF proteins are a conserved family of RNA binding proteins found in all eukaryotes examined so far. This study focussed on PUF5, one of 11 PUF family members encoded in the Trypanosoma brucei genome. Native PUF5 is present at less than 50000 molecules per cell in both bloodstream and procyclic form trypanosomes. C-terminally myc-tagged PUF5 was mainly found in the cytoplasm and could be cross-linked to RNA. PUF5 knockdown by RNA interference had no effect on the growth of bloodstream forms. Procyclic forms lacking PUF5 grew normally, but expression of PUF5 bearing a 21 kDa tandem affinity purification tag inhibited growth. Knockdown of PUF5 did not have any effect on the ability of trypanosomes to differentiate from the mammalian to the insect form of the parasite.